Financial Education and Social Media Financial Information as Determinants of Investment Interest among Bekasi Residents - Alya Nuha Malihah Sahlan; Alya Lutfia Efendi (Lentera Ilmu Nusantara, 2026)
The development of investment in the digital era has driven increasing public interest in participating in investment activities, but the level of financial education and the quality of information received remain major challenges. This study aims to analyze the influence of financial education and social media financial information on investment interest in the Bekasi community. This study used a quantitative approach with a causal design and was analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected through a Likert-scale questionnaire distributed to Bekasi residents who met the research criteria. The analysis results showed that all constructs met the validity and reliability criteria. Structurally, financial education has a positive and significant effect on investment interest, and social media financial information also has a positive and significant effect on investment interest. These findings indicate that improving financial education and providing quality financial information through social media play a significant role in encouraging public investment interest. This research is expected to serve as a reference for regulators and stakeholders in designing more effective financial education strategies and disseminating investment information in the digital era.